2015
DOI: 10.1016/j.jad.2015.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent coping profiles differentiate reports of depression and anxiety symptoms

Abstract: The purpose of the study was to identify groups of adolescents based on their reported use of different coping strategies and compare levels of depression and anxiety symptoms across the groups. Tenth and eleventh grade public school students (N = 982; 51% girls; 66% Caucasian; M age =16.04, SD = .73) completed a battery of self-report measures that assessed their use of different coping strategies, depressive symptoms, and anxiety symptoms. Latent profile analysis (LPA) classified the participants into four d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 58 publications
7
55
0
Order By: Relevance
“…Physiological difficulties sometimes may hide a more severe inner-self fragility that struggles to cope with external pressures of maturation (e.g., more competitive education stages, more complex and intimate relationships, more frequent fights with parents/relatives etc.). 10,11 This mixture of inner fragility and increasing outer changes may represent fertile ground for the development of a mental disease. 12,13 Early detection of these impaired mental states represents a challenge for clinicians and may be the gold standard for prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Physiological difficulties sometimes may hide a more severe inner-self fragility that struggles to cope with external pressures of maturation (e.g., more competitive education stages, more complex and intimate relationships, more frequent fights with parents/relatives etc.). 10,11 This mixture of inner fragility and increasing outer changes may represent fertile ground for the development of a mental disease. 12,13 Early detection of these impaired mental states represents a challenge for clinicians and may be the gold standard for prevention.…”
Section: Introductionmentioning
confidence: 99%
“…The adoption of emotion-focused coping techniques, especially as reflected through the use of music and videos in the present participant sample is indicative of an adaptive way of mood regulation [23,70] in young populations. Moreover, the young people's tendency for wanting to connect with others whilst gaming is indicative of support seeking, which has been recognised as an adaptive functional coping strategy that can help with mood regulation [69,71,72] and has been associated with positive mental health [26].…”
Section: Discussion Principal Findingsmentioning
confidence: 99%
“…Distraction techniques can be adaptive in certain situations and have been associated with positive mental health outcomes in youth [26,67]. However, continual use of adaptive distraction has been associated with low levels of wellbeing and poor mental health outcomes more generally [6][7][8]16,24,68,69], perhaps because long-term distraction can hinder appropriate action responses [28] and may reinforce the persistence of avoidance-escape approaches, the latter having been linked with poor mental health outcomes [26]. The adoption of emotion-focused coping techniques, especially as reflected through the use of music and videos in the present participant sample is indicative of an adaptive way of mood regulation [23,70] in young populations.…”
Section: Discussion Principal Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have shown that certain coping profiles, particularly those that combine approach strategies, are more resilient to stress (Lee, Seo, Lee, Park & Lee, 2016), showing a negative relationship with anxious-depressive symptomatology (Herres, 2015), stress (Nielsen & Knardahl, 2014), and burnout (Martinent & Decret, 2015). However, assuming that the absence of disease does not necessarily indicate well-being (Kaplan, 2005), there is a lack of studies that truly analyze coping profiles with reference to their implications for the well-being of individuals, separate from the psychopathological paradigm.…”
Section: Coping Flexibility and Well-beingmentioning
confidence: 99%